Knowledge and Attitudes about Helsinki Declaration on Patient Safety among Anaesthesiologists in Turkey: A Questionnaire Study - (:unkn) unknown (AVES, 2020)
Objective: The Helsinki Declaration on Patient Safety in Anaesthesiology is an important document for anaesthesiologists. This study aimed to evaluate the knowledge and experiences of anaesthesiologists in Mickey on the Helsinki Declaration on Patient Satitty. Methods: After the ethics committee approval and participants' consent, electronic questionnaires were sent to anesthetists working in Turkey. The questionnaire included 48 questions. Results: The mean age of the participants was 44.28 +/- 8.01 years, and 52.1% were women (n =142). The mean time spent in the field of anesthesiology was 12.83 +/- 7.76 years. The percentage of participants working in private hospitals was 13.4%. A total of 58.5% of the participants were educated on patient safety out of whom 37% said that their knowledge was sufficient, 37.3% said that it was limited, and 3.6% felt that it was insufficient The knowledge of participants about the Helsinki Declaration was sufficient in 31.7%, limited in 39.4%, insufficient in 9.2%, and 19.7% had no knowledge. A total of 27% of participants believed that implementation of the Helsinki Declaration improved patient safety. It has been stated that the minimum patient monitoring standards recommended by the European Board of Anaesthesiology has been complied in operating moms and recovery units (90.8% and 78.2%, respectively). Conclusion: The findings of this survey might guide not only the individual anesthetists but also hospital administrators to develop strategies to improve patient safety and thus quality of care in the light of the recommendations listed in the Helsinki Declaration.
Keywords: Anaesthesiology standards; Helsinki Declaration on Patient Safety; patient safety; quality of healthcare standards